A Survey on Software Testing Education in Brazil - Paschoal, Leo Natan; de Souza, Simone R. S. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Software testing is one of the most important quality assurance activities. However, it is considered a challenge while teaching in undergraduate programs. One of the implied challenges is how to include this topic in computing undergraduate programs and in which level of detail. The industry has recognized the importance of this deeper and more solid formation. Nevertheless, in most cases, teaching software testing is distributed in disciplines and with different levels of detail. Each teaching method of software testing has its own advantages and disadvantages. Understanding this scenario is important for the proposition of improvements and innovations in the way of teaching software testing. This paper presents the results of a survey conducted throughout various Brazilian computing courses in different universities to identify which and how topics on software testing are taught. The objective is to identify the way in which the content is given, the support mechanisms used in the teaching practices, the challenges imposed and the instruments used to evaluate the students' learning. The survey was conducted in November of 2017 with Higher Education Institutions (HEI) lecturers distributed in different regions of Brazil, which have undergraduate programs in computer science. From the results, suggestions are presented and discussed in order to promote the dissemination of knowledge in this area of software engineering.